ANTESEDEN CUSTOMER LOYALTY - Rury Febria Alber (Jurnal Manajemen dan Pemasaran Jasa, 2017)
The purpose of this research is to test and analyze empirically the influence of service quality, customer satisfaction, and trust to loyalty of internet banking users. Researcher choose 280 respondents as the sample of this research, using purposive sampling. The statistical methods used to test the hypothesis are simple linear regression and Structural Equation Model with Partial Least Square (PLS). The result of this research shows that service quality, customer satisfaction, and trust affected loyalty of internet banking users. Based on the results of research that has been done, there are some managerial implications as follows: 1) display on internet banking making easier to understand, 2) service innovation provided by internet banking, 3) improved security system on internet banking and 4) cheaper transactions using internet banking.